Lim (e ^ x + x) ^ (1 / x) x x 0 +?

Lim (e ^ x + x) ^ (1 / x) x x 0 +?
Anonim

תשובה:

#lim_ (x-> 0 ^ +) (e ^ x + x) ^ (1 / x) = e ^ 2 #

הסבר:

#lim_ (x-> 0 ^ +) (e ^ x + x) ^ (1 / x) #

  • # (e + x + x) ^ (1 / x) = e ^ (e ^ x + x) ^ (1 / x)) = e ^ (ln (e ^ x + x / x)

(# 0 +) (# 0) + (= x)# (#) (x-> 0 ^ +) (ln (e ^ x + x)) ') / ((x' ') # # #=#

# # (x-> 0 ^ +) (e ^ x + 1) / (e + x + x) = 2 #

לכן, (x-> 0 ^ +) e ^ (ln (e ^ x + x) / x) = # (x-> 0 ^ +) (e ^ x + x) ^ (1 / x) = lim_

הגדר

#ln (e ^ x + x) / x = u #

# x-> 0 ^ + #

# u-> 2 #

#=# #lim_ (u-> 2) e ^ u = e ^ 2 #